Inter-Relationship between Global Competitiveness and Human Development- Analytical Study of Selected Countries (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research aims to study the inter-relationship between global competitiveness indicators and human development indicators for selected countries (low, middle, and high income)by using Granger Test, and VAR Test. The results of the causality test showed that there is a causality relation between international competitiveness and human development.We found global competitiveness indicators has a clear effect on human development indicators in the low, middle, and high-income countries.